Muhammadiyah Sebagai Gerakan Sosial dan Ekonomi - Krist Wibisono, Adrianto; Satriyo Wibowo, Totok; Muslimin, Khoirul (Penerbit Minhaj Pustaka, 2025)
Indonesia is a country that has many educational histories, especially regarding the history of the development and renewal of Islam. Of the many organizations in Indonesia, the Muhammadiyah movement is one of the largest Islamic movement organizations in Indonesia. With the meaning that in this word Muhammadiyah separately implies as followers of the Prophet Muhammad SAW. On this occasion, research was conducted to find out how Muhammadiyah is a social and economic movement. This type of research is descriptive research, research that is carried out intensively, in detail, and in depth on an individual, institution or certain symptoms with a narrow area or subject. This research was conducted using interviews and documentation methods. The results obtained show that Muhammadiyah is guided by the Al-Qur'an precisely in surah Al-Ma'un as the basis for running in the social realm. Muhammadiyah is an organization that is not only engaged in one field. This can be seen by the existence of institutions under the economic sector that are useful for helping the welfare of Muhammadiyah members and the ummah.